Pembelajaran Biologi dengan Menggunakan Model Predict Observe Explain Terhadap Hasil Belajar Kognitif Siswa - Nining Nuraida Ning; Devie Novallyan; Intan Kartika Shary (JEMST (Jurnal of Education in Mathematics, Science, and Technology), 2022)
The purpose of this study is to investigate whether or not teaching biology to students at SMAN 2 Merangin using the Predict Observe Explain learning model has an effect on the cognitive learning outcomes of students. This study employs a One-Group Preetest-Posttest Design with a quantitative pre-experimental methodology. Total sampling was used, which means that all students in class X IPA 1 which amounted to 22 people were included in the research sample. Learning outcomes were assessed with a 30-question multiple-choice test used as the research instrument. Students' cognitive learning outcomes were calculated by means of a pre-test score of 77.87, a mean post-test score of 81.96, and a significance value of 0.000) <0.05 using a t-test. If the Effect Size is considered to be 0.00 or 50%, then the results show that H_a is accepted and H_o is rejected. That is, the Predict Observe Explain Learning Model has an effect on the cognitive domain of biology learning outcomes for class X IPA 1 SMAN 2 Merangin